Inactivation of GH3.5 by COP1-mediated K63-linked ubiquitination promotes seedling hypocotyl elongation - Yongting Liu; Yinpeng Xie; Dongqing Xu; Xing Wang Deng; Jian Li (Nature Communications)
Abstract CONSTITUTIVELY PHOTOMORPHOGENIC 1 (COP1), which was first discovered as a central repressor of photomorphogenesis in Arabidopsis, destabilizes proteins by ubiquitination in both plants and animals. However, it is unclear whether and how Arabidopsis COP1 mediates non-proteolytic ubiquitination to regulate photomorphogenesis. Here, we show that COP1-mediated lysine 63 (K63)-linked polyubiquitination inhibits the enzyme activity of GRETCHEN HAGEN 3.5 (GH3.5), a synthetase that conjugates amino acids to indole-3-acetic acid (IAA), thereby promoting hypocotyl elongation in the dark. We show that COP1 physically interacts with and genetically acts through GH3.5 to promote hypocotyl elongation. COP1 does not affect GH3.5 protein stability; however, it suppresses GH3.5 activity through K63-linked ubiquitination in the dark, inhibiting the endogenous conversion of IAA to IAA-amino acid conjugates. Further, light regulates IAA metabolism by suppressing the inhibitory effect of COP1 on the function of GH3.5 and its homologs. Our results shed light on the non-proteolytic role of COP1-mediated ubiquitination and the mechanism by which light regulates auxin metabolism to modulate hypocotyl elongation.